USULSÜZLÜK KABAHATİNİN İŞ LEVSELLİĞİ - (:unkn) unknown (My University, 2015)
VUK md.351 vd.da düzenlenmiş olan usulsüzlük kabahatinin amacı, vergi ödevlilerine yasalar temelinde getirilen ş ekli ödevlerin yapılmasını sağlamak ve böylece, bir yandan vergi sisteminin iş leyiş ini gerçekleş tirmek, diğer yandan dürüst vergi mükellefinin haklarını korumaktır. Ancak, bu kabahat yasada o kadar kötü ş ekilde düzenlemiştirki, bu amaçları ne derece gerçekleş tirebileceği tartış maya açıktır.

The purpose of the minor infraction of rules regulated in Art. 351 et. al. TPL is to ensure tax payers to fulfill their formal duties based on the laws and thus functioning of tax system in accordance with the law and on the other hand to protect the rights of the honest tax payers. However, this infraction is regulated in a such poor way that it is open to argument to what extent it can achieve these goals.
(FUNCTIONALITY OF MINOR INFRACTION OF RULES)
Keywords: Tarih